Study a bout the Epidemiology of Vulvo Vaginal Candidiasis (Candida spp.) in Baghdad City (Baghdad Science Journal, 2007)
This Study was conducted to investigate vaginitis in women who live in Baghdad City. Results Revealed that Candida spp. were the causal agent of 38.5% of symptomatic cases the yeasts Candidaalbicans, C.glabrata, C.tropicalis, C.parapsilosis and C.krusei were isolated with the percentage of 38.1, 9.1, 3.9, 2.6, 1.3 respectively also there were 18% of women in control group carrying Candida spp. The direct smear method were not efficient because the percentage of infection was 17.5% comparing with the culture method the sensitivity of direct smear method was 45.5% The percentage of WBC to Epithelial cells was less than one in 76.6% of women.